The Mediating Role of Brand Trust on the Effect of Brand Ambassador to Purchase Decision - Then, Lydia; Isnaini Nuzula Agustin (TIJAB (The International Journal of Applied Business), 2024)
Background: Beauty products from South Korea, such as skincare and makeup, are often considered as having higher quality and providing better results than local beauty products. With technological advances that continue to develop, obtaining skincare product is currently easier and more accessible to young people. Objective: This research aims to examine the factors that influence purchasing decisions in regards to brand trust as a mediator in Korean skincare products. Method: The sampling employed a purposive sampling method to a population in Batam City who aged over 17 years old and used skincare products made in South Korea. This research used Partial Least Square Structural Equation Modeling (PLS-SEM) for hypothesis testing. Results: The research results indicate that brand trust plays an important role in mediating the relationship between brand ambassadors, brand awareness, and price on purchasing decisions. Brand image, brand awareness, and price directly and indirectly influence purchasing decisions. Meanwhile, brand ambassadors only indirectly influence purchasing decisions through brand trust. Keywords: Purchase Decision; Brand Trust; Brand Ambassador; Brand Awareness; Korean Skincare